2012
DOI: 10.1177/1088357612446859
|View full text |Cite
|
Sign up to set email alerts
|

Using Read-Alouds of Grade-Level Biographies and Systematic Prompting to Promote Comprehension for Students With Moderate and Severe Developmental Disabilities

Abstract: The purpose of this study was to investigate the effects of a modified system of least intrusive prompts on text-dependent listening comprehension for four middle-school-aged students with intellectual disability and autism during read-alouds of adapted grade-level biographies. A system of least intrusive prompts was modified by inserting a rule for answering "Wh" questions and an opportunity to hear sections of the biography again. The procedure was evaluated via a multiple probe design across students. Outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
117
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(124 citation statements)
references
References 27 publications
6
117
0
1
Order By: Relevance
“…The findings from the current study also support the existing body of research supporting the use of a modified system of least intrusive prompting to teach comprehension skills to students with moderate intellectual disability (e.g., Browder et al, 2007;Mims et al, 2012). When applied to daily living skills, the system of least intrusive prompting usually provides increasing assistance for making the motoric response by telling, showing, and guiding the student to make the response (e.g., Manley, Collins, Stenhoff, & Kleinert, 2008).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The findings from the current study also support the existing body of research supporting the use of a modified system of least intrusive prompting to teach comprehension skills to students with moderate intellectual disability (e.g., Browder et al, 2007;Mims et al, 2012). When applied to daily living skills, the system of least intrusive prompting usually provides increasing assistance for making the motoric response by telling, showing, and guiding the student to make the response (e.g., Manley, Collins, Stenhoff, & Kleinert, 2008).…”
Section: Discussionsupporting
confidence: 82%
“…The final prompt involved reading the answer itself. While prior research used this modified system of least intrusive prompting to promote listening comprehension during read-alouds (e.g., Mims et al, 2012), the current study employed a system of least intrusive prompting following repeated readings of text read by the participant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Students increased both their engagement with the text and comprehension responses. Mims, Hudson, and Browder (2012) also found that middle school students with moderate intellectual disability learned to answer comprehension questions about biographies adapted from grade-level literature (i.e., summary of original text and some picture symbol support). The intervention also incorporated a prompt hierarchy to help students locate the correct answer, beginning with re-reading smaller portions of the text that contained the answer.…”
mentioning
confidence: 96%